An Assessment of Nueva Ecija University of Science and Technology (NEUST) Civil Engineering Students’ Understanding of Engineering Software: A Case Study - Ballor Cyn B. Ortiz; Joseph Paolo A. Geronimo; Mike Angelo R. Miranda; Jannus Neil L. Cruz; Joefil C. Jocson (International Journal of Progressive Research in Science and Engineering, 2024)
Mastery of structural engineering software is essential for college students studying Civil Engineering, especially at universities such as NEUST (Nueva Ecija University of Science and Technology). This study focuses on the crucial component of comprehending civil engineering software among students in the Civil Engineering curriculum. The Civil Engineering curriculum at NEUST is designed to provide students with a thorough understanding and proficiency in the area. Mastery of structural engineering software is a crucial ability that students must possess in order to succeed in their academic studies and future professional efforts. This research used a case study methodology to assess the current degree of comprehension among NEUST Civil Engineering students about structural engineering software. The project seeks to collect detailed insights into students' experiences and perceptions by conducting questionnaires, interviews, and maybe hands-on assessments. The analysis will primarily aim to identify the strengths, shortcomings, obstacles, and potential for improvement in students' proficiency in using structural engineering software. The results are expected to guide improvements to NEUST's Civil Engineering program, namely by making changes to the curriculum, teaching methods, and resource allocation to better meet the learning needs of students in this important field. Furthermore, the results of this study may have wider ramifications for the field of civil engineering education, offering significant insights into efficient approaches for instructing and acquiring knowledge in structural engineering software inside the academic domain.